Development of Macular Holes after Rhegmatogenous Retinal Detachment Repair in Japanese Patients - Mamiko Shibata; Toshiyuki Oshitari; Fusae Kajita; Takayuki Baba; Eiju Sato; Shuichi Yamamoto (Journal of Ophthalmology)
Purpose. To determine the factors associated with the development of a macular hole (MH) after successful rhegmatogenous retinal detachment (RRD) surgery. Methods. Of 1260 eyes that underwent surgery for RRD between April 2005 and March 2010 in our hospital, the medical records of 4 cases from our hospital and one case from another hospital that had undergone RRD surgery and later developed MH were reviewed. This is a retrospective study. Results. 837 eyes underwent pars plana vitrectomy (PPV) with or without scleral buckling (SB), and 423 eyes underwent SB. The four cases that developed MH had PPV alone and one case had PPV with SB. After including the results of three earlier reports, the mean interval for the MH to develop after SB alone was significantly shorter than after PPV alone or after PPV with SB. Conclusions. The SB procedures might accelerate the development of MH after RRD surgery.